Assessing TVET Leadership Development Programmes: Implications to TVET Leaders - Abdullah, Nor Hazana; Hong, Ching Zhi; Samad, Sam Faheeda; Ahmad, Rabiah (Journal of Technical Education and Training, 2025)
Leadership is a pivotal element in advancing the objectives of Technical and Vocational Education and Training (TVET), especially in the context of higher education institutions tasked with driving workforce readiness and institutional transformation. Despite increased investments in leadership development, many training programmes lack comprehensive evaluation mechanisms beyond initial participant satisfaction. This study assesses the effectiveness of leadership development programmes at Universiti Tun Hussein Onn Malaysia (UTHM), guided by the Kirkpatrick Four-Level Training Evaluation Model. The evaluation focused on Levels 1 (Reaction), 2 (Learning), and 3 (Behavior), encompassing 12 leadership programmes under three clusters: ULead, Hi-Lead, and Hi-Per. A descriptive quantitative approach was used, involving post-training surveys, pre- and post-tests, and supervisor feedback three months post-programme. Findings reveal high participant satisfaction (mean scores between 4.30–4.90), statistically significant learning gains across all tested modules (p < 0.05), and varying degrees of behavioral application, with reported workplace transfer rates ranging from 7.14% to 53.33%. However, inconsistent data collection at Level 3 and in some coaching-based programmes indicates the need for improved follow-up mechanisms. The study underscores the importance of integrating comprehensive evaluation practices within TVET leadership initiatives to ensure programme impact and sustainability.